Pengaruh Metode Pembelajaran Edutainment Terhadap Hasil Belajar Sub Tema Tugasku Sehari-Hari Disekolah Pada Siswa Kelas II SD Negeri 095194 Negeri Bayu - Ica Desria Sinurat (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to determine the influence of edutainment learning methods on the learning outcomes of the sub-theme of my daily tasks at school for class II students at SDN 095194 Negeri Bayu for the 2023/2024 academic year. The type of research used in this research is quantitative research, which states that Quantitative research is research that takes the form of numbers and analyzes using statistics. The research design that will be used is experimental, in the form of a pre-experimental design that uses the "one group pretest posttest design" design. The research sample is class II students at SD Negeri 095194 Negeri Bayu, totaling 20 students, of which 7 are boys and There were 13 women. The instrument used in this research was a test. The results of testing the research hypothesis are that there is a significant influence in this research from the data that has been tested. The data can be seen from the data analysis that the average results of the experimental class were obtained in the pre-test (49.75) and post-test (90). The research results at the 0.05 level based on data analysis of pretest and posttest values ​​show that the sign value (2-tailed) is 0.00 < 0.05, where Ho is rejected and Ha is accepted. So it can be concluded that there is a significant influence on improving the learning outcomes of students who use edutainment learning methods on the learning outcomes of class II students at SD Negeri 095194 Negeri Bayu for the 2023/2024 academic year.